ALAT PEMANTAU PENGOSONGAN AKUMULATOR 12V/ 5Ah BERBASIS ARDUIONO UNO - Putri, Tsamaroh Nidaa; Sasmoko, Priyo (Gema Teknologi, 2016)
Tsamaroh Nidaa Putri, Priyo Sasmoko explains that accumulator is a combination of several pieces of cells used for altering the chemical energy into electricity energy used in motor vehicles. Accumulators are used continuously will shrink and drop so it needs to be recharged. To know the state of the battery voltage drop experienced the need for a measurement to determine the ability of the accumulator. Design manufacture accumulator discharge monitoring tool consists of a voltage divider circuit to know the big accumulator voltage in percentage form. Used also an ACS712 current sensor to detect the discharge current and LM35 temperature sensor to determine the temperature of the accumulator. The control system used is the Arduino UNO microcontroller and an LCD for displaying the measurement data. Normal voltage ranges accumulator 12,5V - 13,8V. Accumulator with a capacity of 5Ah takes 8 hours to process discharge when using 20 watt lamp load. If the voltage of the first accumulator on the LCD shows the percentage of 0 % then automatically the system will work to discharge  for a second accumulator. The duration of use depends on the large accumulator load used. Keyword:Accumulator, ACS712,  capacity accumulator, Arduino UNOReferencesAgustin, Leonandi. 2015. Rancang Bangun Sistem Monitoring Kondisi Aki Pada Kendaraan Bermotor. Skripsi. Universitas Tanjungpura Pontianak.Andri, Helly. 2010.  Rancang Bangun System Battery Charging Automatic. Skripsi S1 Teknik Elektro Fakultas Teknik Universitas Indonesia.Asnan, Zainal. 2007. Alat Pengecekan Kapasitas Aki (Accu) Berbasis Personal Computer. Skripsi. Universitas Katolik Widya Mandala Surabaya.Bishop, Owen. 2004. Dasar-dasar Elektronika. Jakarta: Erlangga, Alih Bahasa Irzam Harmein.Fadli, Usman. 2015. Aplikasi Sensor Arus ACS712 Dan Borland Delphi 7.0 untuk Monitoring Penggunaan Daya Listrik pada Rumah Berbasis Arduino UNO. Tugas Akhir. Universitas Diponegoro.Frank D. Petruzella., 2001, Elektronika Industri. Yogyakarta: Penerbit ANDI, Penerjemah Suminto, Drs. MA.,Kadir, Abdul. 2013. Panduan Praktis Mempelajari Aplikasi Mikrokontroler dan Pemrogamannya Menggunakan Arduino. Yogyakarta: Penerbit ANDI.Marpaung, May Harpri Rabiman. 2014. Monitoring Suhu dengan Menggunakan Sensor Suhu LM35 Serta Pengaturan Suhu Pada Otomatisasi Dispenser Berbasis Arduino UNO dengan Tampilan LCD. Tugas Akhir. Universitas Diponegoro.Salim, Emil. 2014. Perancangan dan Implementasi Telemetri Suhu Berbasis Arduino UNO, Skripsi. Universitas Sumatra Utara.Setiyawan, Danang Duwi. 2015. Pengisi Baterai Akumulator Otomatis Berbasis Mikrokontroller. Tugas Akhir. Universitas Gajah Mada.Tooley, Michael. 2003. Rangkaian Elektronik Prinsip dan Aplikasi. Jakarta: Erlangga, Alih Bahasa Irzam Harmein